Report on the initial experience in small bowel transplantation at São José do Rio Preto Medical School Hospital - Silva, Renato Ferreira da; Paula, Andréia Cristina de; Arroyo Júnior, Paulo César; Gonzales, Adriano Miziara; Marchine, Julio Sérgio; Duca, William José; Rocha, Márcia Fumiê; Felício, Helen de; Abbud-Filho, Mario; Silva, Rita de Cássia da (Brazilian Journal of Transplantation, 2008)
Intestinal failure is the patient’s inability to keep his or her hidroelectrolitic and nutritional support by the digestive way, arisen out of massive enterectomy or diseases in which the bowel is unable of appropriately absorb fluids and nutrients. Patients with intestinal failure associated to short bowel syndrome and other functional diseases that present malabsorption and total parenteral nutrition and related complications (recurrent sepsis and thrombosis of one or more deep venous accesses) are candidates for small bowel transplant, which can be an isolated small bowel transplant, a combined liver/small bowel transplant or a multivisceral one. In our institution, three isolated small bowel transplants were carried out, and they will be reported in this article seeking to describe our initial experience in such transplant.